Financial Literacy and Digital Literacy To Awareness of Investment Scams Among Indonesian College Students - Sabi Ode Umar; Zuliani Dalimunthe (Green Publisher Indonesia, 2024)
This study explores the influence between financial literacy and digital literacy, on investment sacam awareness among university students in Indonesia. Using a quantitative approach and the Structural Equation Model Partial Least Square (SEM-PLS), data was collected from 288 university students from 38 provinces in Indonesia through an online questionnaire survey. The results of the analysis show that both financial literacy and digital literacy have significant indirect effects on investment scam awareness through the mediation of cybercrime awareness. The findings support the importance of a good understanding of financial literacy and digital literacy in countering the risk of investment scams, especially in today's digital era. However, this study also found differences in the effect of financial literacy on investment scam awareness based on economic and non-economic educational backgrounds, highlighting the importance of considering demographic factors in efforts to increase investment scam awareness among university students. These findings make an important contribution to the understanding of investment fraud prevention efforts and highlight the need for a more inclusive educational approach focusing on financial literacy and digital literacy at the higher education level in Indonesia.